Collaborating: Finding Common Ground for Multiparty ProblemsCollaborating: Finding Common Ground for Multiparty Problems, by GrayBarbara San Francisco: Jossey-Bass, 1989, 329 pp., $28.95, cloth. - Kramer, Robert (Academy of Management Review, 1990)
The article presents a review of the book ?Collaborating: Finding Common Ground for Multiparty Problems,? by Barbara Gray.